REINTERPRETATION OF ETHNO-NATIONAL CONFIGURATIONS AS A FRAMEWORK FOR CONFLICT PREVENTION AND RESOLUTION - M Faisal, Pebi Wahyudin; Setiawibawa, Rachmat; Setiawan, Bayu; Uksan, Arifuddin (Yayasan Amanah Nur Aman, 2025)
This article reinterprets Cederman et al.’s (2025) model of ethno-national configurations as not only an explanatory framework for civil and interstate wars but also as a diagnostic tool for conflict prevention and peacebuilding. By integrating theories of nationalism, ethnic conflict, and peace and conflict resolution, the paper demonstrates how state–nation incongruence, captured in five configurations United Home Rule, United Alien Rule, Divided Home Rule, Partial Home Rule (irredentism), and Divided Alien Rule generates different types of grievances and security dilemmas. We argue that these structural typologies can serve two distinct functions: (1) ex post analysis of conflicts, explaining why and how wars emerge; and (2) ex ante diagnosis of latent threats, offering early warning for peace practitioners. The paper further develops a Conflict–Peace Framework that links configurations to specific institutional remedies, ranging from power-sharing and autonomy to cross-border governance and international mediation. The contribution is twofold: (a) bridging political science and peace studies by transforming a conflict-centered typology into a peace-oriented architecture, and (b) proposing an analytical map for both scholars and practitioners to anticipate and resolve ethno-national conflicts.